Implementation of laws Tentang Peraturan Kepolisian No. 7 Tahun 2022 Tentang PTDH Dalam Rangka KEPP - Salman Sahrir; Elvi Susanti Syam; Aburizal Fatwa Ramli; Muhammad Natsir (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2026)
This study aims to determine and analyze the Role of the Police in enforcing the Code of Ethics of the Republic of Indonesia National Police at the Parepare Police Station who were convicted according to Police Regulation No. 7 of 2022 and the factors causing PTDH (Dishonorable Dismissal) against Police Members at the Parepare Police Station. This study uses a normative empirical research method with a legislative and social approach. The data sources used are primary and secondary data. Funding analysis will be conducted using a qualitative prescriptive approach. The results of this study are the Role of the Police in Enforcing the Code of Ethics of the Republic of Indonesia National Police at the Parepare Police Station, which is Criminalized According to Police Regulation Number 7 of 2022, is by serving complaints/reports related to violations by members of the National Police/PNS Polri, Organizational and Internal Security, Advocacy of leadership and service to the community, professional and proportional law enforcement by upholding Law and Human Rights and increasing internal consolidation in an effort to harmonize enforcement of regulations for police members and Factors Causing Dishonorable Dismissals Against the National Police at the Parepare Police Station because the police member in question has been proven to have committed a crime of narcotics abuse and also previously committed a crime of Domestic Violence (KDRT).